SINTESIS DAN KARAKTERISASI KOMPOSIT KAOLIN-TiO2 DARI ILMENIT BANGKA UNTUK FOTODEGRADASI ZAT WARNA RHODAMIN B - Rezalia Annisa; Verry Andre Fabiani; Nurhadini Nurhadini (Department of Chemistry - Universitas Bangka Belitung, 2021)
The synthesis and characterization of kaolin-TiO2 from ilmenite composite as a degradation of rhodamine B dye was prepared. Natural kaolin from Air Bara, Central Bangka and ilmenite from BPM Unit Metalurgi PT. Timah (Persero), Tbk., Mentok Bangka Belitung. The kaolin sample was chemically activated and the ilmenite was carried out leaching with acid (HCl), then the ilmenite was calcined at temperature of 700°C to obtain the anatase phase. Synthesis of kaolin-TiO2 from ilmenit using the precipitation method using ethanol as a solvent, the composite using with 3 variation of kaolin mass i.e 0,2; 0,4 and 0,6 (w/w). The fungsional groups and the phase structure of kaolin-TiO2 from ilmenite was analyzed using FTIR and XRD, then the composite was applied to rhodamine B solution to determine the percentage of degradation in the solution by UV-Vis Spectrophotometry analysis. Degradation was carried out by adding 150 mg kaolin-TiO2 to 25 mL of rhodamine B solution and degradation process by irradiating UVC light. Based on FTIR and XRD data should that kaolin-TiO2 from ilmenite was formed composite. The optimum variation of kaolin mass in the composite composition of 0,4:3 (w/w). Based on UV-Vis Spectrophotometry data, rhodamine B solution with composite kaolin-TiO2 as catalyst was able to degrade rhodamine B up to 87,7% with the largest percentage of degradation at the 40 minutes. Keyword : ilmenite, kaolin, kaolin-TiO2, degradation, rhodamine B